2017
DOI: 10.1017/s1751731116001397
|View full text |Cite
|
Sign up to set email alerts
|

A carvacrol–thymol blend decreased intestinal oxidative stress and influenced selected microbes without changing the messenger RNA levels of tight junction proteins in jejunal mucosa of weaning piglets

Abstract: Recent studies indicate that intestinal oxidative stress and microbiota imbalance is involved in weaning-induced intestinal dysfunction in piglets. We have investigated the effect of feeding a carvacrol-thymol blend supplemented diet on intestinal redox status, selected microbial populations and the intestinal barrier in weaning piglets. The piglets (weaned at 21 days of age) were randomly allocated to two groups with six pens per treatment and 10 piglets per pen. At weaning day (21 days of age), six piglets w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
81
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(96 citation statements)
references
References 45 publications
(47 reference statements)
7
81
3
Order By: Relevance
“…Weaning and weaning-associated intestinal inflammation generate large amount of reactive species. Jejunum reactive oxygen species increase threefold, and thiobarbituric acidreactive substances increase 50% in 28-day-old weaned pigs compared with pre-weaning pigs (Wei et al, 2017). Similar results were reported by Zhu et al (2012) in that the concentrations of nitric oxide and hydrogen peroxide were significantly increased after weaning.…”
Section: Antioxidant Nutritionsupporting
confidence: 83%
See 1 more Smart Citation
“…Weaning and weaning-associated intestinal inflammation generate large amount of reactive species. Jejunum reactive oxygen species increase threefold, and thiobarbituric acidreactive substances increase 50% in 28-day-old weaned pigs compared with pre-weaning pigs (Wei et al, 2017). Similar results were reported by Zhu et al (2012) in that the concentrations of nitric oxide and hydrogen peroxide were significantly increased after weaning.…”
Section: Antioxidant Nutritionsupporting
confidence: 83%
“…Zeng et al (2017) remarked that perturbations of the microbiota are commonly observed in diseases involving inflammation in the GIT, with the inflamed microenvironment being particularly conducive to overgrowth of Enterobacteriaceae, which acquire fitness benefits while other families of symbiotic bacteria succumb to environmental changes. A recent study by Wei et al (2017) reported an increased concentration of reactive oxygen species in the intestine coupled with an expansion of the E. coli population 7 days after weaning. Overgrowth of E. coli induces further inflammation and activation of the immune system, which in turn generates more free radicals, and undermines its functions (Catoni et al, 2008).…”
Section: Antioxidant Nutritionmentioning
confidence: 97%
“…It is noteworthy that the CV–TH blend increased Lactobacillus spp. while decreasing the Enterococcus and E. coli populations (Wei et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Transportation is a crucial factor influencing intestine structure and function, meat quality and slaughter efficiency in pigs (Zou et al, 2017). It has been demonstrated that transport stress may induce intestinal oxidative stress, which contributes to intestinal dysfunction (Wei, Xue, Zhou, & Peng, 2017). Gastrointestinal tract caused by transport stress may increase the risk of bacterial translocation, leading to poor meat quality, high morbidity and epidemic of infectious diseases (Simons, Hill, Swart, Kelly, & Snary, 2016).…”
Section: Discussionmentioning
confidence: 99%